Wartości w orędziach noworocznych polskich, rosyjskich i niemieckich przywódców w latach 2012-2015 - Noińska, Marta (Przegląd Wschodnioeuropejski, 2018)
The aim of the article is to analyze the axiological aspect of the New Year’s addresses of Polish, Russian and German leaders in the context of the sociopolitical situation in recent years. New Year’s messages are abundant with verbal and non-verbal signs that refer to addressee’s values instilled by years of education. The role of homeland, family and work usually underlined. The analyzed speeches evoke patriotic feelings as well as pride in one’s country and encourage cooperation for the good of the state. In the studied material, numerous expressions emphasizing the role of unity are to be found. Despite many similarities, the analyzed New Year’s addresses show some variation in the axiological layer, especially with regard to tolerance and Europeanism. Also, the selection of historical events mentioned by the leaders differs significantly in the studied speeches.